Determining the Effect of Typical South African Production Systems, Pre Slaughter Feed Withdrawal and Post-Slaughter Electrical Stimulation on Beef Tenderness - L. Frylinck; K. Y. Modika; P. E. Strydom; E. C. Webb (Research Aspects in Agriculture and Veterinary Science Vol. 5, 2022)
This study compared the inherent meat tenderness of South African breed-types under typical South African commercial abattoir practices (Phase 1). Phase 2 evaluated meat tenderness and calpain system differences of A-age (feedlot and pasture) animals, AB-age (feedlot and pasture) animals, and B-age (pasture) animals under the determined ideal slaughter conditions for South African crossbred beef breeds. Feed was withdrawn for either three hours or 24 hours pre-slaughter. Within each feed withdrawal group, three electrical stimulation (ES) treatments were applied, viz. ES for 15 seconds, 120 seconds or no stimulation. The carcasses were placed in chillers at 4 ºC within 1 hour after slaughter. In Phase 2, the effect of animal age and feeding regime were investigated using animals of A-age (feedlot and pasture), AB-age (feedlot and pasture) and B-age (pasture). All carcasses were electrically stimulated for 15 seconds. pH and temperature measurements were recorded early post mortem and at 24 hours post mortem. The effect of ageing on meat characteristics was tested on 1 day, 7 days and 14 days post mortem from samples removed from the m. longissimus lumborum (LL) muscle. The ideal post-slaughter procedure was identified as ES-15 electrical stimulation where pH decline was controlled (not too rapidly) by applying electrical stimulation for a short period. Longer feed withdrawal period increased dark-firm-dry (DFD) meat occurrence (pHu >6) in the Nguni and Simmentaler-cross. Brahman-cross longissimus (LL) tended to be more tender with paler colour and higher drip loss when 120 ES was applied. Electrical stimulation of 15 seconds during Phase 2 showed that none of the carcasses were exposed to heat or cold shortening. Longer feed withdrawal recorded higher Warner Bratzler shear force (WBSF) than three hour feed withdrawal. However, ES neutralized the effect of stress on tenderness. On average, the AB-age feedlot animals produced the most tender LL followed by the B-age pasture and A-age feedlot which was similar to the AB-age pasture. A-age pasture animals produced the least tender LL steaks. The calpain proteolytic system played a pivotal role in determining the ultimate meat tenderness and although connective tissue becomes less soluble in older animals it did not play the determinant role in tenderness in this study. The intramuscular fat (< 3%) played an important role in the tenderness outcome of Nguni LL which marbled well at AB-age. Judging eating quality on the grounds of age alone is not reliable, because carcasses from older animals were not necessarily tougher than those of younger animals. The South African classification system and resultant remuneration should be revisited and consumers should be educated accordingly. Production systems should be optimised by using ideal pre- and post-slaughter conditions and adapted to accommodate different breed-types.